Vestibular Rehabilitation Therapy and Corticosteroids for Vestibular Neuritis: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Hanik Badriyah Hidayati; Hana Aqilah Nur Imania; Dinda Sella Octaviana; Roy Bagus Kurniawan; Citrawati Dyah Kencono Wungu; Ni Nengah Rida Ariarini; Cempaka Thursina Srisetyaningrum; Delvac Oceandy (Medicina, 2022)
Background and Objectives: Besides corticosteroids, clinicians found that vestibular rehabilitation therapy (VRT) has a potential effect on vestibular neuritis (VN) improvement. This study aimed to investigate the efficacy of both corticosteroid therapy (CT) compared to VRT, and each group compared to their combination (CT vs. (CT+VRT) and VRT vs. (CT + VRT). Materials and Methods: Systematic searches were performed in PubMed, CINAHL, and Scopus for randomized controlled trials (RCTs) reporting the administration of at least CT and VRT for VN. The outcome of interest was VN’s subjective and objective improvement parameters. Results: Four RCTs involving a total of 182 patients with VN were eligible for systematic review and meta-analysis. The weighted mean difference (WMD) of canal paresis (objective parameter) in the CT group is significantly lower than in the VRT group after a 1 month follow-up (8.31; 95% CI: 0.29, −16.32; p = 0.04; fixed effect). Meanwhile, the WMD of Dizziness Handicap Inventory (DHI) (subjective parameter) in the VRT group is significantly lower than in the CT group after a 1 month follow-up (−3.95; 95% CI: −7.69, −0.21; p = 0.04; fixed effect). Similarly, the WMD of DHI in the combination group (CT+VRT) is significantly lower than in the CT group after a 3 month follow-up (3.15; 95% CI: 1.50, 4.80; p = 0.0002; fixed effect). However, there is no significant difference in all outcomes after 12 months of follow-ups in all groups (CT vs. VRT, CT vs. combination, and VRT vs. combination). Conclusions: This study indicates that CT enhances the earlier canal paresis improvement, as the objective parameter, while VRT gives the earlier DHI score improvement, as the subjective parameter. However, their long-term efficacy does not appear to be different. VRT has to be offered as the primary option for patients with VN, and corticosteroids can be added to provide better recovery in the absence of its contraindication. However, whether to choose VRT, CT, or its combination should be tailored to the patient’s condition. Future studies are still needed to revisit this issue, due to the small number of trials in this field. (PROSPERO ID: CRD42021220615).